A Long‐Term (2012–2024) Data Set of Integrated Land–Atmosphere–Carbon–Hydrology Interactions Observations in Ningxiang, East Monsoon Region - Ruichao Li; Zhenghui Xie; Binghao Jia; Zhipeng Xie; Longhuan Wang; Yuhang Tian; Heng Yan; Yanbin You (Geoscience Data Journal, 2025)
ABSTRACT The eastern monsoon region of China, characterised by its high population density and rapid economic development, is particularly sensitive to global climate change. Issues such as water scarcity, droughts and floods, as well as ecological and environmental degradation, are particularly pronounced in this region. Consequently, there is a significant scientific imperative to investigate the land, atmosphere, carbon and hydrology interactions within this region. It is imperative for enhancing the efficiency of water usage, elucidating the evolutionary mechanisms of the carbon and hydrological cycles and evaluating ecological and environmental impacts. In this context, the present study introduces an integrated observation platform of the land–atmosphere–carbon–hydrology interactions in the eastern monsoon region—Ningxiang Station of the Institute of Atmospheric Physics, Chinese Academy of Sciences, and provides a long‐term (2012–2024) integrated observation data set of the land–atmosphere–carbon–hydrology interactions. The integrated observation data set comprises hourly basic meteorological elements, half‐hourly flux data and half‐hourly groundwater depth data. These continuous, long‐term, and high‐resolution data sets have been employed to investigate land–atmosphere–carbon–hydrology interactions in the eastern monsoon region. Furthermore, the data set provides a critical foundation for the development of a new generation high‐resolution earth system models and for advancing understanding of the impacts and feedback mechanisms of natural processes and anthropogenic activities on water, energy, material exchanges and climate. The complete data set is publicly accessible via the Science Data Bank (https://doi.org/10.57760/sciencedb.20182).